Sistem Informasi Pengelolaan Data Jasa Pembangunan Rumah Hunian Berbasis Web Pada PT. Novavil Mutiara Utama - Nur Azizah; Anis Mirza (CV. Multi Kreasi Media, 2024)
Along with the rapid development of technology, home construction service providers to carry out construction planning can take advantage of the development of computer-based technology. The rapid development of development in Indonesia has had a very influential impact in the field of home construction services. Construction Service Providers are contractors who work on the real estate project. PT. Novavil Mutiara Utama is a company engaged in contractor services. Based on the results of work observations and company project report documents, it can be concluded that PT. Novavil Mutiara Utama there are problems that occur in the data management process for residential house construction which is less efficient in seeing the progress of the work. PT. Novavil Mutiara Utama there are problems that occur in the data management process, including the need for tools to inform project work data in real-time and tools that can reduce the number of use of report documents that must be filled out and can find out the budget costs that must be spent to carry out development activities.